Tree Consciousness in Tarun Tapasi - Chalise, Keshav Raj (Literary Studies, 2024)
Being conscious means being aware of something. Trees, in a general argument, are not ostensibly aware of the things in the way humans do but modern forest and environmental studies have concluded that trees are most certainly more aware than we think them to be. Consciousness can be a general awareness of being alert and conscious of one’s environment, and fully experiencing what happens all around. It can equally be a self-awareness of being able to identify the purpose and effect of others and on others. One may argue that trees do not have a brain to identify what is good and what is bad, and therefore they are not conscious. However modern theories of relational metaphysics and environmental biology have identified the features of consciousness in trees. This is the theory of plant science and plant consciousness. Like relational metaphysics, literature has established the principle that trees have consciousness and therefore they can feel, communicate, and express. Keeping the theory of environmental study as the tool, this research examines the point of how Tarun Tapasi, a tree sage has a complete sense of consciousness. Kavisiromani Paudyal has seen life, sensation, feeling, awareness, and the knowledge of ethics and humanity in the tree, and therefore he has chosen the tree as his means of expression in the form of a young sage in the epic, Tarun Tapasi. This study recognizes how the tree has realized the sense of growth, pain, suffering, and sensation in him and how he has felt the loss of ethics and humanity in human beings. Tarun Tapasi, a tree is incredibly aware of the social, moral, and sensational feelings not less than a fully conscious human being is. With these features of the highest level of cognizance, the Tapasi tree is a sage and a conscious being.